VIRAL EPIZOOTIC REVEALS INBREEDING DEPRESSION IN A HABITUALLY INBREEDING MAMMAL - Ross‐Gillespie, Adin (Evolution, 2007)
Inbreeding is typically detrimental to fitness. However, some animal populations are reported to inbreed without incurring inbreeding depression, ostensibly due to past “purging” of deleterious alleles. Challenging this is the position that purging can, at best, only adapt a population to a particular environment; novel selective regimes will always uncover additional inbreeding load. We consider this in a prominent test case: the eusocial naked mole‐rat (Heterocephalus glaber), one of the most inbred of all free‐living mammals. We investigated factors affecting mortality in a population of naked mole‐rats struck by a spontaneous, lethal coronavirus outbreak. In a multivariate model, inbreeding coefficient strongly predicted mortality, with closely inbred mole‐rats (F≥ 0.25) over 300% more likely to die than their outbred counterparts. We demonstrate that, contrary to common assertions, strong inbreeding depression is evident in this species. Our results suggest that loss of genetic diversity through inbreeding may render populations vulnerable to local extinction from emerging infectious diseases even when other inbreeding depression symptoms are absent.